Pentingnya Identitas dan Integritas Seorang Guru Kristen - Ramses Simanjuntak (SANCTUM DOMINE: JURNAL TEOLOGI, 2018)
In teaching activities a teacher not only pay attention to teaching techniques and appearance only. He also has to pay attention to other key issues, namely his identity and integrity as a teacher. Good teachers show their identity and integrity to their students, especially their identity and integrity as a Christian teacher. It must be understood that a Christian teacher whose job it is to educate is a teacher who in him must have consistency in the actions, values, methods, measures, principles, expectations and the resulting things which are visible It is clear that the quality, the nature, or the circumstances that exhibit a unified whole so as to have the potential and ability that radiate authority; Honesty and unity of thoughts, words and deeds to create a reputation and trust.